Kinesiotherapy for Post-stroke Rehabilitation： Analysis of Characteristics of Clinical Trials in the Past 20 Years Based on Clinical Trials Registry Platform - WANG Hui; FENG Yuting; YU Yongpei; HU Chenhua; TAO Liyuan (康复学报)
ObjectiveTo analyze the characteristics of clinical trials related to kinesiotherapy in post-stroke rehabilitation in the registration platforms of www.clinicaltrials.gov and www.chictr.org.cn over the past 20 years.MethodsClinical trials of kinesiotherapy for post-stroke rehabilitation published on the above registration platforms from January 1, 2002 to January 28, 2022 were searched, and relevant information was collected and statistically analyzed.ResultsA total of 1 027 clinical trials related to kinesiotherapy for post-stroke rehabilitation were retrieved, and 823 eligible studies were included. The clinical trials registered in this field have been increasing year by year, and the number of studies (977) registered in American registry platforms is significantly higher than that in China (50). Randomized controlled design was the main clinical trial design (79.47%), followed by single-arm objective performance criteria (OPC) design (16.04%) and non-randomized controlled design (4.01%). In the methods of blinding, the proportion of trials with outcomes assessor masking was the highest (37.91%), followed by open trial label (28.92%) and single blind design (14.70%). Most of the trials had a sample size less than 50 cases (58.69%), and 85.54% of trials had a sample size less than 100 cases. In terms of the types of intervention, equipment intervention accounted for the main type (42.41%), and the proportion of trials with equipment interventions increased in the last 10 years compared with those in the previous 10 years, with statistical difference between groups (P<0.05). In terms of geographical distribution, most of the studies were conducted in the Americas (35.97%, mainly in the United States), but the number of registered studies in the Americas declined in recent 10 years, while the number of registered studies in Europe and Asia increased, with statistical difference among different geographical locations (P<0.001). The main intervention measure with the highest proportion was robot-assisted rehabilitation (15.43%), followed by integrative treatment (13.73%), virtual reality (6.93%), and the main evaluation indexes were scores of motor function scales (42.53%) and motor function test (23.69%).ConclusionThe clinical trials related to kinesiotherapy of post-stroke rehabilitation are in a period of rapid growth, which is related to current trends with emphasis on the early rapid recovery of sensory and motor abilities and activities of daily living in the medical field, which will greatly improve the quality of life of patients after stroke. However, there are still limitations such as insufficient sample size and low proportion of studies on emerging interventions.